Samoregulacja biznesowa w zakresie etyki biznesu firm zachodnich jako odpowiedź na łamanie praw pracowniczych w Chinach - Sroka, Robert (Człowiek i Społeczeństwo, 2018)
Robert Sroka. Samoregulacja biznesowa w zakresie etyki biznesu firm zachodnich jako odpowiedź na łamanie praw pracowniczych w Chinach [Business self-regulation in terms of business ethics of Western companies as a response to violation of employee rights in China] edited by W. Banach, M.A. Michalski, J. Sójka, „Człowiek i Społeczeństwo” vol. XLVI: Między Chinami a Zachodem. Pytanie o źródła chińskiego sukcesu gospodarczego [Between China and the West. An inquiry into the sources of the Chinese economic miracle], Poznań 2018, pp. 145–158, Adam Mickiewicz University. Faculty of Social Sciences Press. ISSN 0239-3271. Salary that does not meet basic life needs, working conditions that threaten life and health, employing children, forced labor, lack of freedom of association, long hours of work, destroying the environment, widespread corruption is just the beginning of a long list of unethical behaviors of companies in China, as well as Western companies producing in China. Under the pressure of non-governmental organizations and consumer boycotts in Europe and the USA, business self-regulatory initiatives have been created to raise working conditions at Chinese suppliers. The most popular self-regulations initiatives in terms of business ethics are: Ethical Trade Initiative (ETI), Business Social Compliance Initiative (amforiBSCI), Social Accountability 8000 (SA8000), International Council of Toy Industries (ICTI). Conducting research on self-regulation in the field of business ethics of Western companies operating in China, I analyze three issues. The first is to describe the source of the need to apply such self-regulatory initiatives, which is the outsourcing business strategy. The second element is to define the minimum rules that are broken due to the use of an outsourcing strategy. The third point of consideration is the presentation of the self-regulatory initiatives.